2005
DOI: 10.1021/bi0476331
|View full text |Cite
|
Sign up to set email alerts
|

Anion Binding Properties of Reduced and Oxidized Iron-Containing Superoxide Dismutase Reveal No Requirement for Tyrosine 34

Abstract: We report the first spectroscopic observation of substrate analogue binding to the reduced state of iron superoxide dismutase from Escherichia coli (Fe 2+ SOD) and demonstrate that the pH dependence reflects inhibition of anion binding by ionized Tyr34, not loss of a positive contribution on the part of Tyr34's labile proton. This can also explain the pH dependence of the K M of Fe 2+ SOD. Thus, it appears that substrate binding to Fe 2+ SOD occurs in the second sphere and is not strongly coupled to hydrogen b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
48
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 45 publications
10
48
0
1
Order By: Relevance
“…Moreover, Tyr34 is responsible for the reduced state active site pK near 8.5 and exerts important control over substrate specificity (17,19,(39)(40)(41). In both mutants, Fe coordination geometry almost identical to that of the WT-FeSOD is retained (below).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Tyr34 is responsible for the reduced state active site pK near 8.5 and exerts important control over substrate specificity (17,19,(39)(40)(41). In both mutants, Fe coordination geometry almost identical to that of the WT-FeSOD is retained (below).…”
Section: Resultsmentioning
confidence: 99%
“…When azide is added to Y34F-Mn 3+ -SOD the enzyme resembles the low temperature six-coordinate N 3 -Mn 3+ -SOD complex, and shows no temperature dependence(71). Thus, the “gateway” tyrosine seems to play a critical role in controlling anion access to the metal site in both Fe- and Mn-SODs(15, 16, 71) by inhibiting anion binding at the metal center. The same function for Y9 appears to be a feature of NiSOD catalysis.…”
Section: Discussionmentioning
confidence: 99%
“…In this mechanism the inactive inhibitor-bound enzyme is six-coordinated, while the active form remains five-coordinated, with substrate binding causing the displacement of one of the manganese ligands. A third proposed mechanism suggested that the catalytic reaction occurs through an outer sphere mechanism and instead utilizes an alternate anion-binding site in the active site, possibly at the base of the funnel [216218]. This proposal is based upon various anions inhibiting the activity of FeSOD, but without directly coordinating the metal center.…”
Section: Manganese and Iron Superoxide Dismutasesmentioning
confidence: 99%